2022
DOI: 10.3390/cells11121900
|View full text |Cite
|
Sign up to set email alerts
|

Complex Role of Microbiome in Pancreatic Tumorigenesis: Potential Therapeutic Implications

Abstract: Pancreatic cancer (PC) is the fourth leading cause of cancer-related mortality with limited diagnostic and therapeutic options. Although immunotherapy has shown promise in the treatment of several cancers, its role in pancreatic cancer is rather limited. Several studies have focused on determining the role of the tumor microenvironment with cancer-cell-intrinsic events and tumor-infiltrating immune cellular properties. However, in the past decade, there has been emerging research aimed at delineating the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 109 publications
1
0
0
Order By: Relevance
“…Previous human research studies reported a possible link between the oral microbiota and carcinogenesis in different organs, including the gastrointestinal tract, the head and neck, the oral cavity, and the pancreas [7][8][9][10][11]. In line with these findings, a positive association of a higher diversity of microbiota with Haemophilus, Porphyromonas, Leptotrichia, and Fusobacteria compared to healthy adults with pancreatic cancer has been observed in large cohort human studies [12,13]. Additionally, investigations into Lactobacillus and Streptococcus genera (oral bacteria) have shown that they generate volatile sulfur compounds, short-chain fatty acids (SCFAs), reactive oxygen species, reactive nitrogen species, hydrogen peroxide, and lactic acid, all of which are implicated in carcinogenesis, chronic inflammation, genomic instability, tumor angiogenesis, and GC progression [14].…”
Section: Introductionsupporting
confidence: 68%
“…Previous human research studies reported a possible link between the oral microbiota and carcinogenesis in different organs, including the gastrointestinal tract, the head and neck, the oral cavity, and the pancreas [7][8][9][10][11]. In line with these findings, a positive association of a higher diversity of microbiota with Haemophilus, Porphyromonas, Leptotrichia, and Fusobacteria compared to healthy adults with pancreatic cancer has been observed in large cohort human studies [12,13]. Additionally, investigations into Lactobacillus and Streptococcus genera (oral bacteria) have shown that they generate volatile sulfur compounds, short-chain fatty acids (SCFAs), reactive oxygen species, reactive nitrogen species, hydrogen peroxide, and lactic acid, all of which are implicated in carcinogenesis, chronic inflammation, genomic instability, tumor angiogenesis, and GC progression [14].…”
Section: Introductionsupporting
confidence: 68%